Micro-structural Studies of Thermosonic Cu-Al Bonding Interface - Thangaraj, Joseph Sahaya Anand; Chua, Kok Yau; Jalar, Azman (Trans Tech Publications, 2014)
Thermosonic Copper (Cu) wire interconnection has been under an extensive research and development to replace expensive Gold (Au) wire material in the semiconductor industry. However, a reliability concern is raised due to void formation at the bonding interface of Copper wire-Aluminum bond pad (Cu-Al) after High Temperature Storage (HTS) annealing condition. It is believed that the Intermetallic Compound (IMC) layer growth and evolution lead to a volumetric shrinkage which in turn results in the void formation. Annealing conditions influence the development of the IMC at the bonding interface which is related to the bonding reliability. In this work, the effects of annealing toward the micro-structure and IMC growth at the bonding interface were evaluated using Scanning Transmission Electron Microscope equipped with Energy Dispersive X-ray analysis. In the as-synthesized sample bonded at 100°C, an inhomogeneous IMC formation dominated by grain boundary diffusion was observed. After High Temperature Storage of 1000 hours, the consumption of the Al bond pad resulted in the formation of irregular IMC layers. The variation of phases existed in a localized region was believed due to simultaneous growth of IMC by both grain boundary and volume diffusions. Moreover, the diffusion of Cu into Si was observed. This resulted in the formation of the mixture of Si + η” phases in the affected sea region.